PEAK DEBIT ANALYSIS USING SYNTHETIC UNIT HYDOGRAPHIC METHOD ITB 1 AND HEC-RAS VERSION 5.0.7 (Case Study of Manna Downstream watershed) - Syahroni, Muhamad (Inersia: Jurnal Teknik Sipil, 2021)
Flooding is a natural disaster caused by the discharge or volume of water that flows in a river exceeds its stream capacity. One of the causes of the flood is high rainfall. The discharge of a river flow depends on the rainfall that falls in a watershed. The purpose of this study was to determine the peak discharge due to the intensity of rainfall in the downstream of Air Manna Watershed and determine the point that will undergo runoff on the Air Manna river flow. This study used Synthetic Unit Hydrograph (HSS) ITB 1 method and analyzed used HEC-RAS 5.0.7. From the result of hydrological analysis used the HSS ITB 1 method, it was found out the peak discharge in the downstream of Air Manna Watershed for return periods 2, 5, 10, 25, 50 and 100 years was 1322.21 m3/s, 1492.94 m3 /s, 1594 12 m3 /s, 1712.20 m3/s, 1794.33 m3 /s, and 1872.85 m3/s. After analyzing used HEC-RAS 5.0.7 software, Air Manna river was unable to accommodate the flow rate that occurred and undergo runoff along the flow.